Therapeutic observation of transcutaneous auricular vagus nerve stimulation for chronic migraine in pediatric patients: a case report - Weng, Siqi; Xue, Yao; Xiao, Xuezhen; Hocher, Berthold; Zhang, Yishui; Yang, Xiaowei; Liu, Qirui; Ji, Yabin (Frontiers in Pain Research, 2025)
BackgroundAlthough interest in migraine has increased in recent years, important gaps remain in understanding and optimizing its management. These gaps are particularly pronounced in pediatric migraine, which continues to be understudied.Case reportThis case report demonstrates the efficacy and safety of transcutaneous auricular vagus nerve stimulation (taVNS) in an 8-year-old male patient with refractory chronic migraine with aura [two to three weekly episodes; visual analog scale (VAS): 5–9; duration of each episode was 24 h]. After discontinuing all prophylactic and abortive medications (except ibuprofen suspensions such as Motrin®), the patient underwent a 28-week taVNS protocol that involved the following phases: a 4-week acute intervention, a 4-week intermission period, a 12-week preventive intervention, and an 8-week follow-up. During the acute intervention phase, the patient’s headache duration decreased by 84.4%, and frequency was reduced to fewer than two episodes/week, with complete aura resolution. The preventive intervention yielded further improvement to fewer than 1 episode/week by week 8 (with a 37.5% reduction in medication use). At final follow-up, the patient maintained a medication-free status with only three mild episodes (VAS: 1–3; duration <30 min) in the last 4 weeks. No adverse events were observed.ConclusiontaVNS was effective and safe in the management of chronic migraine in the reported pediatric patient. These findings suggest the need for further evaluation of this non-pharmacological intervention in pediatric migraine.